Pd-Catalyzed Functionalization of Aryl Amines on a Soluble Polymer Support - Santos, A. Sofia; Marques, M. Manuel B. (Synlett, 2020)
Herein we report the use of a soluble polymer support PEG-2000 on Pd-catalyzed reactions to improve the functionalization of aromatic amines and the synthesis of N-heterocycles. Compatibility of metal-catalyzed reactions for assembling privileged structures such as functionalized anilines were studied. PEG-supported anilines were found to be suitable substrates for Pd-catalyzed N-arylation, Sonogashira and Heck reactions. PEGylated substrates were prepared in yields up to 94%. This work consists on a proof of concept on the use of PEGylated anilines on Pd-catalyzed cross-coupling reactions. Indole core was attained in 82% and 62% yields, via two different routes.
Keywords: aryl amine; metal-catalyzed; PEG; functionalization; anilines